Ідентифікація стейхолдерів процесу підвищення енергоефективності у житлово-комунальному господарстві - Павленко, Н. М. (Ways to Improve Construction Efficiency, 2012)
Considered are the main interested parties (stakeholders) at the national and local levels of the process of energy saving in housing and communal services of Ukraine. Identification of the stakeholders will make it possible to conduct a stakeholder analysis to determine the capacity and willingness of stakeholders to participate in the process of enhancing the efficiency of housing and communal services.